DETERMINAN KREATIVITAS PEGAWAI, PERAN MEDIASI KNOWLEDGE SHARING - Khorij Fastian Wibowo; Suhana Suhana (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
Bank Indonesia is responsible for maintaining monetary stability, strengthening financial system resilience, and ensuring the effectiveness of the payment system. Amid increasing economic complexity and the rapid digitalization of the financial sector, fostering employee innovation and creativity has become essential to support effective policy implementation and operations. This study aims to analyze the influence of transformational leadership and psychological empowerment on employee creativity, with knowledge sharing as a mediating variable. A quantitative approach was employed through a survey of 100 employees from the Cash Management Work Unit, selected using convenience sampling. The findings indicate that: (1) transformational leadership does not have a direct effect on employee creativity; (2) psychological empowerment has a strong positive effect on creativity; (3) knowledge sharing positively contributes to creativity; (4) transformational leadership positively influences knowledge sharing; (5) psychological empowerment positively influences knowledge sharing; (6) knowledge sharing mediates the relationship between transformational leadership and creativity; and (7) knowledge sharing mediates the effect of psychological empowerment on creativity. Theoretically, these findings suggest that employee creativity is primarily driven by psychological empowerment through knowledge-sharing mechanisms. Practically, enhancing creativity requires strengthening psychological empowerment and cultivating a culture of knowledge sharing. Future research is recommended to expand contextual scope and methodological approaches to obtain more comprehensive results.